Analysis of coiled stator ultrasound motor: Fundamental study on analysis of wave propagation on acoustic waveguide for coiled stator. (1st June 2018) - Ozeki, Seiya; Kurita, Keisuke; Uehara, Choyu; Nakane, Noriaki; Sato, Toshio; Takeuchi, Shinichi
Abstract: In our research group, we previously developed a coiled stator ultrasound motor (CS-USM) for medical applications such as intravascular ultrasound (IVUS) devices. However, wave propagation on acoustic waveguides has not been investigated sufficiently in previous studies. In this study, we analyze the propagation velocity of elastic waves from the simulated the vibration displacement mode profile along a straight line acoustic waveguide via three-dimensional finite element method (FEM). Concerning results, elastic waves with vibration displacement along the thickness direction show dispersion characteristics corresponding to the a0 and a1 mode plate waves (Lamb waves) in the acoustic waveguide. Our theoretical hypotheses of the propagation velocities were closely borne out by experimental results. We further find that the dispersion characteristic is affected by the width of the acoustic waveguide. We believe that our findings can contribute to improved CS-USM designs for practical application.